KNOWING STUDENT'S PERSONALITY TYPES IN THE DETERMINATION OF CAREER SELECTION ACCORDING TO HOLLAND'S THEORY - Siti Hafsoh; A. Muri Yusuf; Afdal (Literasi Nusantara, 2021)
This paper is a scientific paper that aims to identify the personality types of students in determining career choices according to Holland's theory. The need to know yourself, personality and recognize interests and talents that are more dominant before a career direction is set. Because currently there are still many people who don't know their personality type when they first choose curry. In the end, the career that is being carried out does not match his own personality, this has an impact on one's career success. Knowing the student's personality type is very important, so that we can help and direct students in making career choices according to their respective personalities. The method used in this article is literature research. which discusses theories related to the topic of liberation obtained from relevant sources. The results of this discussion will allow teachers to direct their students about the appropriate personality according to their respective personalities.